A heteroditopic NHC and phosphine ligand supported ruthenium(ii)-complex: an effective catalyst for the N-alkylation of amides using alcohols. Issue 12 (18th May 2022) - Donthireddy, S. N. R.; Singh, Vivek Kumar; Rit, Arnab
Abstract : A heteroditopic Ru(ii )-bis-NHC complex in combination with dppe was developed as an effective catalyst system (0.2 mol% loading) for the N -alkylation of amides and selective mono-/di-alkylation of 4-aminobenzamide derivatives in excellent yields. Abstract : A ruthenium(ii ) complex of a chelated heteroditopic N -heterocyclic carbene ligand in combination with a phosphine ligand was uncovered to be a highly effective catalyst for the N -alkylation of diverse amides using readily available primary alcohols. A wide range of secondary amides was thus obtained in excellent yields (up to 98%) employing a low catalyst (2c ) loading of 0.2 mol% and a substoichiometric amount of base. The 1 H NMR and ESI-MS analyses support the participation of a N -heterocyclic carbene and phosphine supported Ru–H species in the catalytic cycle and the mechanistic studies including the deuterium labelling experiment suggest the involvement of a borrowing hydrogen protocol. Additionally, the present catalytic system was also revealed to be efficient for the selective mono-alkylation and unsymmetrical di-alkylation of 4-aminobenzamides which have not been studied before to the extent of our knowledge.